Exploring Pathways Related to Men's Violence: A Qualitative Exploration of the Relationship between Violent Men's Violence and Their Masculinities, Childhood, and Emotions. Issue 10 (3rd October 2019) - Jansson, Peter Martin
ABSTRACT: This study explored new ways of finding knowledge about violent men's pathways toward their status as violent criminals and the mechanisms that underlie their violent behavior. The empirical data were gathered through biographical interviews with 10 men sentenced to therapy against violence and drugs at a Swedish treatment center. The men who had experienced violence and childhood maltreatment tended to bypass shame with uncontrolled anger and violence when reliving childhood traumas. Conversely, men without extreme childhood experiences seemed to exhibit more controlled violence mechanisms. Two men who had experienced brutal physical school bullying might have been expected to bypass shame with immediate violence; however, these men described their violence as controlled, suggesting that they had learnt to take cognitive control over their bypass mechanisms in order to escape the bullying.